Pendidikan Perennialisme : Membangun Pemikiran Kritis di Era Digital - Dori Omas Hasibuan; Hadi Kurniawan; Herlini Puspika Sari (Journal of Creative Student Research, 2024)
In the digital era filled with abundant information, students must learn to think critically. The perennialism approach to education, which emphasizes deep learning and enduring principles, can be very helpful in cultivating critical thinking skills. This research finds ways in which perennialism can be incorporated into contemporary education curricula by analyzing literature and educational practices. The results show that this method not only enhances students’ understanding of philosophical and ethical concepts but also improves their ability to analyze and evaluate various information available in the digital world. Therefore, it is hoped that the application of perennialism in education can serve as a useful method to prepare students to face intellectual challenges in the era of computers and the internet. The findings indicate that perennial education encourages students to engage in in-depth discussions, critically analyze classical texts, and reflect on modern ethical issues. This method encourages students not only to acquire information but also to question, analyze, and evaluate arguments within the complex digital context of the current era. This research concludes that perennialism can be an effective method for building critical thinking skills and preparing students to actively participate in the information society.